Facile fabrication and tribological properties of self-lubricating polyurethane materials with sponge-like structure - B. P. Yang; J. B. Cui; B. Mu; J. F. Cui; J. H. Guo; X. Wang (eXPRESS Polymer Letters, 2019)
Inspired by the lubrication mechanism of human articular cartilage tissue, the porous self-lubricating polyurethane (PU) materials with micron-meter pore were fabricated by non-solvent induced phase separation (NIPS) method with 60 wt% N,N-dimethylformamide (DMF) as a coagulation agent. The scanning electron microscopic (SEM) images demonstrated that the cross-section morphology of the materials is similar to that of the sponge and adjacent macropores were connected by interpenetrating pores to exhibit an ‘ink-bottle’ type pore structure. Meanwhile, the porosity of the porous self-lubricating PU materials could be controlled by adjusting the PU solution concentrations and the oil content increased as the increasing of porosity. The results of centrifugation/heating test indicated that the porous self-lubricating PU materials have an excellent oil retention performance owing to the pore structure. The tribological properties of porous self-lubricating materials with different porosity under various loads and sliding velocities were investigated by a block-on-ring wear tester which revealed that excellent friction reduction and wear resistance properties of the porous self-lubricating materials were achieved by the lubricating oil squeezed from pores which the friction coefficient of the materials significantly reduced, from 0.174 to 0.078 with the increases of oil content. Furthermore, the lubrication mechanism of porous self-lubricating PU material was discussed as well.